STOCK POWER: Uncovering the Effect of Asset Structure, Sales Growth, and Business Risk on Share Prices with the Support of Capital Structure as a Regulator - Ariyanti, Rina (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
This study aims to determine the effect of Asset Structure, Sales Growth and Business Risk on Stock Prices with Capital Structure as a moderating variable. This type of research is quantitative associative. The sampling method with the "purposive sampling" method is to select samples with certain considerations. The company's sample consists of 29 companies listed on the LQ 45 index. Data processing techniques using the E-Views Version 10.0 program use descriptive statistics, two-model tests, model tests, classical assumption tests, hypothesis tests, and determination coefficient tests. The results showed that simultaneously Asset Structure, Sales Growth and Business Risk had a positive effect on Share Price. Capital Structure does not moderate the relationship between Asset Structure, Business Risk, Sales Growth and Share Price.